ChemInform Abstract: New Rotenoids and Coumaronochromonoids from the Aerial Part of Boerhaavia erecta. Issue 47 (4th November 2013) - Do, Thi My Lien; Truong, Anh Vu; Pinnock, Travis George; Pratt, Lawrence Michael; Yamamoto, Shigeki; Watarai, Hitoshi; Guillaume, Dominique; Nguyen, Kim Phi Phung
Abstract Two new coumaronochromanoids, (I) and (III), and three new rotenoids, (II), (IV), and (V), are isolated from the title plant, together with ten known compounds.